SCM STRATEGY FOR FISHERMEN’S OPERATIONAL PERFORMANCE IN KENDARI: SCOR AND AHP APPROACHES - Setyawati, Indri; Zulfadlih, La Ode Sahlan; Muslimin, Yuliana; Putra M, Eka Dharma (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The city of Kendari has significant marine fisheries potential, supported by continuously increasing capture fisheries production each year; however, this growth has not been accompanied by efficient distribution or increased added value for local fishers. Key challenges include the weak bargaining position of fishers, fluctuating selling prices, and limited supporting infrastructure such as cold storage and refrigerated transportation, all of which indicate weak implementation of Supply Chain Management in the fisheries sector. This study aims to analyze the condition of SCM in the operational performance of fishers’ businesses in Kendari’s coastal areas and to formulate effective SCM implementation strategies using the SCOR Model and the Analytical Hierarchy Process (AHP). The findings show that distribution efficiency remains low, with an average loss of selling value of 20–30% due to reduced fish quality during distribution. AHP analysis identifies priority strategies to strengthen SCM, including increasing cold storage capacity (priority weight 0.35), providing transparent price information (0.27), establishing supply chain institutions based on fishers’ cooperatives (0.22), and offering SCM management training for fishers (0.16). These strategies are expected to improve distribution efficiency, enhance the bargaining position of fishers, and promote the economic empowerment of local communities, thereby supporting sustainable fisheries development in Kendari.